Developing Writing Self-Efficacy: Perspectives from Agricultural Communications Students - Haley M. Banwart; Shuyang Qu (Journal of Applied Communications, 2023)
While there is mounting consensus writing is an essential skill required of agricultural communications graduates, there are opposing views as to what educators can do to improve students’ writing education and performance. Self-efficacy research provides one perspective for exploring the relationship between students’ performance and their beliefs in their writing abilities. The purpose of this study was to qualitatively explore how agricultural communications students perceive their writing self-efficacy and what underlying sources shape their self-efficacy beliefs. The findings confirmed agricultural communications students use a variety of sources to inform their self-efficacy beliefs including their interpretations of their writing performance and education; interactions with modeling and assignment expectations; feedback messages and their perceived value of writing; feelings of anxiety and optimism; self-regulated learning strategies, such as prewriting and drafting processes; different types of writing, such as academic writing versus industry writing; and different types of courses, including agricultural science and communications courses. Overall, the results were consistent with previous writing self-efficacy studies, however the differentiation between the types of courses students enroll in provided a new direction for self-efficacy research. Recommendations for practice are provided on enhancing agricultural communications students’ writing self-efficacy and improving writing instruction. Future research is needed to determine how other cognitive, behavioral, and environmental influences impact writing development.
Keywords: self-efficacy; writing skills; agricultural communications